How I treat metastatic triple-negative breast cancer. (13th May 2019) - Caparica, Rafael; Lambertini, Matteo; de Azambuja, Evandro
Abstract : Triple-negative breast cancer (TNBC) is associated with a high risk of recurrence and generally a bad prognosis. More than one-third of patients with TNBC will present distant metastases during the course of their disease. Although chemotherapy has been the main treatment option for metastatic TNBC for a long time, this scenario has changed recently with the advent of the polyadenosine diphosphate-ribose polymerase inhibitors (PARPis) for patients harbouring a mutation in the BRCA genes (BRCAmut) and also with the results of immunotherapy in patients with PD-L1-positive tumours. The present manuscript proposes a treatment algorithm for patients with metastatic TNBC based on the currently available, most relevant literature on the topic. For patients with a BRCAmut and able to tolerate chemotherapy, we recommend initiating treatment with platins (carboplatin/cisplatin) and to start PARPis at disease progression. For patients with PD-L1-positive tumours (PD-L1 expression on tumour-infiltrating immune cells ≥1%), we recommend first-line treatment with nab-paclitaxel and atezolizumab, when available. In patients without a BRCA mutation and with PD-L1-negative tumours, we recommend single-agent chemotherapy with taxanes (paclitaxel or docetaxel) as a first-line treatment. In patients with a high disease burden or who are very symptomatic, combinations such as anthracyclines plus cyclophosphamide or platins with taxanes are valid options. Chemotherapy should be maintained until the occurrence of disease progression or limiting toxicities. After progression to first-line chemotherapy, anthracyclines are an option for patients who received taxanes and vice versa. For patients who progressed to taxanes and anthracyclines, or who present contraindications to these agents, fluorouracil/capecitabine, eribulin, gemcitabine, cisplatin/carboplatin, vinorelbine and ixabepilone are alternatives. The treatment of TNBC is constantly evolving, and the inclusion of patients in ongoing trials evaluating new targeted agents, immunotherapy and predictive biomarkers should be encouraged, in an attempt to improve metastatic TNBC treatment outcomes.